The role of gender and sexual experience in predicting adolescent condom use intentions using the theory of planned behaviour - Rich, A.; Mullan, Barbara; Sainsbury, Kirby; Kuczmierczyk, A. (Taylor & Francis Group, 2014)
Objectives: To examine how the prediction of condom-related cognitions, intentions, and behaviour amongst adolescents may differ according to gender and sexual experience within a theory of planned behaviour (TPB) framework. Methods: Adolescents (N = 306) completed questionnaires about sexual experience, condom use, TPB variables, perceived risk, and safe sex knowledge. Results: Significant differences in TPB variables, perceived risk, and knowledge were found; males and sexually experienced participants were generally less positive about condom use. Twenty percent of the variance in attitudes was accounted for by four variables; specifically, female gender, no previous sexual experience, better safe sex knowledge, and greater risk perceptions were associated with more positive attitudes. The prediction of intentions separately amongst sexually experienced (R 2 = 0.468) and inexperienced (R 2 = 0.436) participants revealed that, for the former group, attitudes and subjective norms were the most important considerations. In contrast, among the inexperienced participants, attitudes and the gender-by-perceived risk interaction term represented significant influences. Conclusions: The results suggest that interventions designed to improve adolescents’ intentions to use condoms and rates of actual condom use should consider differences in gender and sexual experience.